2023
DOI: 10.2196/49284
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Music-Based Mindfulness Intervention for Black Americans With Elevated Race-Based Anxiety: A Multiple-Baseline Pilot Study

Abstract: Background Race-based anxiety is a substantial health issue for the Black community. Although mindfulness interventions have demonstrated efficacy for alleviating anxiety, three central barriers prevent Black Americans from accessing existing mindfulness treatments: high costs, excessive time commitments, and limited cultural relevance. There is a need for novel mindfulness interventions for the Black community that can overcome these barriers. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…Consistent with our hypothesis, we found evidence that “healing attempt” decreased anxiety and increased mindfulness/self-compassion in our sample; additionally, the intervention received strong feasibility and acceptability ratings as well. These results are in line with our prior 2 feasibility studies of “healing attempt,” which also found the intervention to decrease state anxiety and increase mindfulness/self-compassion with high feasibility and acceptability [ 30 , 31 ]. Thus, this study adds to the evidence that “healing attempt” may be a feasible intervention for race-based anxiety in the Black community and inspires future research to more deeply investigate this possibility.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with our hypothesis, we found evidence that “healing attempt” decreased anxiety and increased mindfulness/self-compassion in our sample; additionally, the intervention received strong feasibility and acceptability ratings as well. These results are in line with our prior 2 feasibility studies of “healing attempt,” which also found the intervention to decrease state anxiety and increase mindfulness/self-compassion with high feasibility and acceptability [ 30 , 31 ]. Thus, this study adds to the evidence that “healing attempt” may be a feasible intervention for race-based anxiety in the Black community and inspires future research to more deeply investigate this possibility.…”
Section: Discussionsupporting
confidence: 89%
“…Our team previously conducted 2 studies examining the feasibility of “healing attempt” for treating race-based anxiety in Black Americans [ 30 , 31 ]. Both prior studies used a multiple baseline design consisting of repeatedly assessing state anxiety (ie, momentary anxiety) and state mindfulness/self-compassion and comparing changes in these metrics across two time-periods: (1) an initial baseline period with no intervention (ie, the “control” period) and (2) an experimental period where the intervention is administered [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We replicated and extended our initial findings and showed that "healing attempt" can improve anxiety and mindfulness/self-compassion with high feasibility/acceptability [8]. Congruent with the existing literature, the observed improvements in mindfulness/self-compassion may have driven the reductions in anxiety [2,9].…”
Section: Discussionsupporting
confidence: 71%
“…Our team previously conducted 2 studies examining the feasibility of "healing attempt" for treating race-based anxiety in Black Americans [30,31]. Both prior studies used a multiple baseline design consisting of repeatedly assessing state anxiety (ie, momentary anxiety) and state mindfulness/self-compassion and comparing changes in these metrics across two time-periods:…”
Section: Introductionmentioning
confidence: 99%